POCT Detection of Pseudomonas aeruginosa by PGM and Application of Preventing Nosocomial Infection of Bronchoscopy - Tao Wen; Houqi Ning; Yinping Yang; Jinze Zhang (Journal of Analytical Methods in Chemistry)
Background. The primary pathogen responsible for bronchoscope contamination is Pseudomonas aeruginosa. Conventional techniques for bronchoscopy disinfection and pathogen identification methods are characterized by time-consuming and operation complexly. The objective of this research is to establish a prompt and precise method for the identification of Pseudomonas aeruginosa, with the ultimate goal of mitigating the risk of nosocomial infections linked to this pathogen. Methods. The magnetic nanoparticles (MNPs) were synthesized in a single step, followed by the optimization of the coating process with antibodies and invertase to produce the bifunctionalized IMIc. Monoclonal antibodies were immobilized on microplates for the specific capture and enrichment of Pseudomonas aeruginosa. Upon the presence of Pseudomonas aeruginosa, the monoclonal antibodies, the test sample, and the IMIc formed sandwich structures. The subsequent addition of a sucrose solution allowed for the detection of glucose produced through invertase hydrolysis by a personal glucose meter, enabling quantitative assessment of Pseudomonas aeruginosa concentration. Results. TEM image demonstrates that the MNPs exhibit a consistent spherical shape. NTA determined that the grain diameter of magnetic nanoparticles was 200 nm. FTIR spectrum revealed the successful modification of two carboxyl groups on the MNPs. The optimization of the incubation pH of the microplate-coated antibody was 7. The optimization of the incubation time of the microplate-coated antibody was 2 h. The optimization of the ligation pH for the polyclonal antibody was 5. Reaction times of polyclonal antibodies linked to magnetic beads was 1 h. The pH of invertase linked by magnetic beads was 4. Conclusion. This article presents a novel qualitative and quantitative immunoassay for point-of-care monitoring of P. aeruginosa utilizing PGM as a readout. The PGM represents a convenient and accurate quantitative detection method suitable for potential clinical diagnostic applications.